The Ancient Persian Form of the First Mongol Dynasties’ Legitimation - N.A. Filin; .R. Gibadullin; E.B. Boev (Золотоордынское обозрение)
Research objectives: To examine the ancient Persian tradition of legitimation of rule by the first Mongol dynasties. Materials: Medieval primary source texts of Abu ʾl-Qasim Ferdowsi, Nizam al-Mulk, Abu Hamid al-Ghazali, Shihab al-Din Suhrawardi, Rashid al-Din, and Abu Bakr Qalandar. Results and novelty of the research: Despite the fact that before the adoption of Islam, the Mongol dynasties used their own forms of legitimization of their rule, based on gaining the right to power and special grace from the heavenly god, Tengri, the Ilkhanids (Hulaguids), ruling in the Near and Middle East (from 1256 to 1353), and the Jochid rulers of various states in the Eastern Europe, Central Asia and Western Siberia (from the 13th to 17th century), who ruled in the Desht-i-Qipchaq, actively used elements of the ancient Persian concept of power, based on special divine light bestowed upon the ruler – Farr. This was accompanied by images of just rulers and the use of traditional titulature of Iranian rulers – the “king” (Shah) and the “king of kings” (Shah-i Shahan). Testimonies to this practice can be found both in the works of philosophers and historians of the period of these Mongol dynasties (for example, in the “Qalandar-name” of Abu Bakr Qalandar) and in the illustrations of the “Shahnameh” from the 14th century that portrayed the Mongolian khans in the image of ancient Persian heroes. This means that, on the one hand, the first Mongol dynasties felt some lack of legitimacy in the conquered territories, on the other hand that there was a desire of the autochthonous elites to link the new rulers to the political culture that had existed before their arrival. As concerns the Jochids, what can be asserted is the spread of an Iranian type of political culture after the migration of urban populations from the area of Persia into the Desht-i-Qipchaq.